Prolonged Alprazolam Treatment Alters Components of Glutamatergic Neurotransmission in the Hippocampus of Male Wistar Rats-The Neuroadaptive Changes following Long-Term Benzodiazepine (Mis)Use - Marina Zaric Kontic; Milorad Dragic; Jelena Martinovic; Katarina Mihajlovic; Zeljka Brkic; Natasa Mitrovic; Ivana Grkovic (MDPI AG, 2023)
Alprazolam (ALP), a benzodiazepine (BDZ) used to treat anxiety, panic, and sleep disorders, is one of the most prescribed psychotropic drugs worldwide. The side effects associated with long-term (mis)use of ALP have become a major challenge in pharmacotherapy, emphasizing the unmet need to further investigate their underlying molecular mechanisms. Prolonged BDZ exposure may induce adaptive changes in the function of several receptors, including the primary target, gammaaminobutyric acid receptor type A (GABAAR), but also other neurotransmitter receptors such as glutamatergic. The present study investigated the potential effects of prolonged ALP treatment on components of glutamatergic neurotransmission, with special emphasis on N-Methyl-D-aspartate receptor (NMDAR) in the hippocampus of adult male Wistar rats. The study revealed behavioral changes consistent with potential onset of tolerance and involvement of the glutamatergic system in its development. Specifically, an increase in NMDAR subunits (NR1, NR2A, NR2B), a decrease in vesicular glutamate transporter 1 (vGlut1), and differential modulation of excitatory amino acid transporters 1 and 2 (EAAT1/2, in vivo and in vitro) were observed, alongside a decrease in α1-containing GABAAR following the treatment. By describing the development of compensatory actions in the glutamatergic system, the present study provides valuable information on neuroadaptive mechanisms following prolonged ALP intake.